State-level climate obstruction and discourses of climate delay: insights from Arizona - Eskridge-Aldama, Phoenix (Frontiers in Climate, 2025)
This study applies the discourses of climate delay (DCD) framework developed by Lamb et al. (2020) to analyze Arizona legislative discourse surrounding House Bill 2686 (2020) and House Bill 2101 (2022), both of which had significant implications for state-level climate governance. Using qualitative discourse analysis of public hearing transcripts, I identify rhetorical strategies that obstruct climate action, particularly those used by utility representatives and their allies. The analysis reveals that delay tactics most often emphasized the negative consequences of climate action and promoted non-transformative solutions, especially those aligned with fossil fuel interests. In contrast, “redirect responsibility” and “surrender” strategies were used less frequently, and “whataboutism” was notably absent. This absence suggests that, in Arizona, obstruction is less about shifting blame and more about affirming local identity and resisting perceived external influence. Based on these findings, I propose an expansion of the DCD framework to include a new subcategory—“pride, identity, and culture”—to capture how regional cultural values influence climate discourse. This study contributes to climate policy scholarship by demonstrating how localized rhetorical strategies sustain climate inaction and by offering a refined framework for future research on discursive climate obstruction.